2011
DOI: 10.1186/1471-2164-12-132
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression throughout a vertebrate's embryogenesis

Abstract: BackgroundDescribing the patterns of gene expression during embryonic development has broadened our understanding of the processes and patterns that define morphogenesis. Yet gene expression patterns have not been described throughout vertebrate embryogenesis. This study presents statistical analyses of gene expression during all 40 developmental stages in the teleost Fundulus heteroclitus using four biological replicates per stage.ResultsPatterns of gene expression for 7,000 genes appear to be important as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 36 publications
1
49
2
Order By: Relevance
“…(Incardona et al, 2012), biomarkers of xenobiotic exposure such as CYP1A inducibility and DNA damage (Jewett et al, 2002;Jung et al, 2011;Raphael et al, 2014), xenobiotic metabolism in vivo (e. g., the aryl hydrocarbon receptor pathway (Bello et al, 2001;Denison and Nagy 2003;Hahn et al, 2004)), altered gene expression (Leaver et al, 2010) (Fisher and Oleksiak 2007;Bozinovic et al 2011;Oleksiak et al 2011;Garcia et al 2012;Bozinovic et al 2013), and genotypic effects Oleksiak, 2008, 2011a,b). Those studies investigated pollution's influences on natural populations at molecular, biological, and ecological levels and helped to elucidate evolved tolerance in polluted populations.…”
Section: Discussionmentioning
confidence: 98%
“…(Incardona et al, 2012), biomarkers of xenobiotic exposure such as CYP1A inducibility and DNA damage (Jewett et al, 2002;Jung et al, 2011;Raphael et al, 2014), xenobiotic metabolism in vivo (e. g., the aryl hydrocarbon receptor pathway (Bello et al, 2001;Denison and Nagy 2003;Hahn et al, 2004)), altered gene expression (Leaver et al, 2010) (Fisher and Oleksiak 2007;Bozinovic et al 2011;Oleksiak et al 2011;Garcia et al 2012;Bozinovic et al 2013), and genotypic effects Oleksiak, 2008, 2011a,b). Those studies investigated pollution's influences on natural populations at molecular, biological, and ecological levels and helped to elucidate evolved tolerance in polluted populations.…”
Section: Discussionmentioning
confidence: 98%
“…To date, only limited genomic and transcriptomic studies on fish embryos and yolksac larvae have been conducted in a few teleost fish species: in zebrafish, Danio rerio, (Packham et al 2009;Ton et al 2002), in gilthead seabream (Ferrareso et al 2008;Sarropoulou et al 2005b), in cod (Drivenes et al 2012;Johansen et al 2011) and in the marine killifish, Fundulus heteroclitus, (Bozinovic et al 2011). To our knowledge, only the EST collections generated for halibut (Douglas et al 2007) and…”
Section: Discussionmentioning
confidence: 99%
“…Filteau et al (2013) 18 found that a set of coexpressed genes differentiated the two whitefish morphotypes, implicating Bone morphogenesis protein (BMP) signaling in the development of ecological differences in tropic morphology. One approach to identify pathways related to function or morphological differences is to study gene expression during development 19, 20 .…”
Section: Introductionmentioning
confidence: 99%